2021
DOI: 10.1021/acs.jpcc.0c10804
|View full text |Cite
|
Sign up to set email alerts
|

Potential-Dependent Superlubricity of Ionic Liquids on a Graphite Surface

Abstract: The lubricities of four quaternary phosphonium ionic liquidstrihexyl­tetradecyl­phosphonium bis­(2,4,4-trimethylpentyl)­phosphinate ([P6,6,6,14]­[(iC8)2PO2]), trihexyltetradecyl­phosphonium bis­(2-ethylhexyl)­phosphate ([P6,6,6,14]­[BEHP]), trihexyltetradecyl­phosphonium bis­(trifluoromethyl­sulfonyl)­imide ([P6,6,6,14]­[TFSI]), and tributylmethyl­phosphonium bis­(trifluoro­menthyl­sulfonyl)­imide ([P4,4,4,1]­[TFSI])were measured as a function of potential on highly oriented pyrolytic graphite (HOPG) by usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 63 publications
1
18
0
Order By: Relevance
“…It has been demonstrated that a certain lateral ordering of an IL develops, which, e.g., enhances lubricity by forming crystal-like structures on ionophilic surfaces, depending on the polarity of the matrix [44][45][46]. This has also been shown for carbon surfaces under an applied potential [40,47,48].…”
Section: Introductionmentioning
confidence: 82%
“…It has been demonstrated that a certain lateral ordering of an IL develops, which, e.g., enhances lubricity by forming crystal-like structures on ionophilic surfaces, depending on the polarity of the matrix [44][45][46]. This has also been shown for carbon surfaces under an applied potential [40,47,48].…”
Section: Introductionmentioning
confidence: 82%
“…Superlubricity, which refers to a near-zero increase in friction with load, is achieved for (i) a [P 6,6,6,14 ] + -enriched Stern layer at −1.0 V, where long alkyl chains associated with [P 6,6,6,14 ] + cations assist the formation of robust boundary layers via enhancing lateral cohesive forces and (ii) a [TFSI] − -enriched Stern layer at +1.0 V, where the bulky fluorinated ligands reduce geometric contact corrugations and form a smooth and flat boundary layer. 93 One key barrier to the commercialization of pure ILs as lubricants on a large scale is high cost. However, their tunable nature means that ILs can be customized to be oil-miscible by introducing long alkyl chains to both cations and anions.…”
Section: Effect Of the Edl On Electrochemicalmentioning
confidence: 99%
“…If one of the sliding surfaces is an electrode, the ion composition of the boundary layer can be controlled by applying a potential and, through this, the lubricity. This makes trobotronics (the active external control of friction) achievable with ILs. , As shown in Figure , the lateral force (friction) changes as the compositions of the Stern layers switch from cation-enriched to anion-enriched when the potential changes from negative to positive. Superlubricity, which refers to a near-zero increase in friction with load, is achieved for (i) a [P 6,6,6,14 ] + -enriched Stern layer at −1.0 V, where long alkyl chains associated with [P 6,6,6,14 ] + cations assist the formation of robust boundary layers via enhancing lateral cohesive forces and (ii) a [TFSI] − -enriched Stern layer at +1.0 V, where the bulky fluorinated ligands reduce geometric contact corrugations and form a smooth and flat boundary layer …”
Section: Effect Of the Edl On Electrochemical Applications Of Ionic L...mentioning
confidence: 99%
See 1 more Smart Citation
“…Our group has also investigated ILs under confinement , using MD simulations, and in ref we developed the peaks and antipeaks analysis for reflectivity; the ideas introduced in ref were later expanded and applied to the study of diamond-confined molten alkali chloride salts . The literature on the structure of ILs using other surface sensitive techniques is vast, and a full set of citations is beyond the scope of this work, but particularly important has been the pioneering work by Baldelli et al using sum frequency generation as well as Perkin et al , and Atkin et al using force microscopy. …”
Section: Introductionmentioning
confidence: 99%